PROSES PEMBELAJARAN TARI PEGI MANTANG MENGGUNAKAN AUDIO VISUAL DI KELAS VII A SMPN 3 TUNGKAL ILIR - Diana Nurlailatul Masruroh; Dedy Firmansyah; Rully Rochayati (Universitas Hamzanwadi, 2025)
This study discusses how the Pegi Mantang dance learning process uses audio-visual media in class VII A of SMPN 3 Tungkal Ilir. This study aims to determine and describe the Pegi Mantang dance learning process using audio-visual media. This study uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of the study on Pegi Mantang dance learning using audio-visual media in the learning process include introductory activities, core activities, and closing activities. Before conducting learning activities, teachers had three stages, namely planning, implementation, and evaluation. Before teachers conducted learning in the classroom, they made lesson plans so that learning in the classroom would run according to the planned objectives. Teachers had teaching modules and ATP as guidelines for teaching, which contained the learning flow and learning objectives compiled by the teachers. Before starting the lesson, the teacher prepares audio-visual media such as a laptop connected to a projector, a projector to display images or dance videos, and speakers for sound amplification. This study found that students learn more effectively when using audio-visual media because they can directly see the dance lessons, which are interesting. By using audio-visual media, students can understand the material more easily and become more skilled and motivated.